Microtubule self-repair. (February 2021) - Théry, Manuel; Blanchoin, Laurent
Abstract: The stochastic switching between microtubule growth and shrinkage is a fascinating and unique process in the regulation of the cytoskeleton. To understand it, almost all attention has been focused on the microtubule ends. However, recent research has revived the idea that tubulin dimers can also be exchanged in protofilaments along the microtubule shaft, thus repairing the microtubule and protecting it from disassembly. Here, we review the research describing this phenomenon, the mechanisms regulating the removal and insertion of tubulin dimers, as well as the potential implications for key functions of the microtubule network, such as intracellular transport and cell polarization.